Pengaruh Integritas Mahasiswa Motivasi Belajar Pemahaman Akuntansi dan Penyalahgunaan Teknologi Informasi Terhadap Perilaku Kecurangan Akademik (Studi Kasus pada Mahasiswa Akuntansi di Kota Malang) - Masruroh, Hanik; Diana, Nur; Fakhriyyah, Dewi Diah (Universitas Islam Malang, 2023)
This study aims to obtain empirical evidence of the influence of student integrity, learning motivation, understanding of accounting and misuse of information technology on academic fraud behavior. The location of this research was accounting students at Brawijaya University, Islamic University of Malang, State University of Malang, Islamic University of Maulana Malik Ibrahim Malang. The sample method used is the purposive sampling method and uses the slovin technique in calculating the number of samples so that a total of 88 respondents are obtained. The results of this study state that Student Integrity, Learning Motivation, Accounting Understanding and Misuse of Information Technology have a simultaneous effect on academic fraud behavior. Student Integrity partially has a positive and significant effect on academic fraud behavior, Learning Motivation partially has no effect and is not significant on academic fraud behavior, Accounting Understanding partially has a positive and significant effect on academic fraud behavior, Information Technology Misuse partially has a positive and significant effect on academic cheating behavior.Keywords: Student integrity, learning motivation, understanding of accounting, misuse of information technology, academic fraudulent behavior.